2022
DOI: 10.1002/cbin.11922
|View full text |Cite
|
Sign up to set email alerts
|

HELQ suppresses migration and proliferation of non‐small cell lung cancer cells by repairing DNA damage and inducing necrosis

Abstract: HELQ plays a key role in DNA damage response and cell-cycle checkpoint regulation. It has been implicated in ovarian and pituitary tumors and may play a role in germ cell maintenance. This study investigated the role of HELQ in lung cancer. The expression of HELQ in patients with non-small-cell lung cancer (NSCLC) was downregulated compared with normal human lungs. Clinical prognostic analysis of Kaplan-Meier plots revealed that patients with NSCLC with low HELQ levels had a reduced overall survival. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Under normal conditions, HELQ is abundantly expressed in healthy human tissues, especially in the reproductive system, where it plays an important role in maintaining germ cell viability through RAD51 paralog-dependent repair. In addition, recent studies have reported that HELQ is abnormally expressed in various cancers (86)(87)(88)(89)(90). HELQ is important for cell proliferation, metastasis and chemotherapy resistance by regulating various molecular signaling pathways (for example, the NER, CHK1-RAD51 and ATM/ATR pathways).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under normal conditions, HELQ is abundantly expressed in healthy human tissues, especially in the reproductive system, where it plays an important role in maintaining germ cell viability through RAD51 paralog-dependent repair. In addition, recent studies have reported that HELQ is abnormally expressed in various cancers (86)(87)(88)(89)(90). HELQ is important for cell proliferation, metastasis and chemotherapy resistance by regulating various molecular signaling pathways (for example, the NER, CHK1-RAD51 and ATM/ATR pathways).…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphism variants of HELQ have been associated with an increased risk of various cancers, including upper aerodigestive tract cancers (78,79), esophageal squamous cell carcinoma (80,81), head and neck cancers (82), gastric adenocarcinoma (81), and breast and ovarian cancer (OV) (83-85) through genome-wide association studies (Table III). Furthermore, there is accumulating evidence indicating that HELQ may act as a tumor suppressor for several cancers, such as osteosarcoma (86), OV (12,13,34,77,87), chronic lymphocytic leukemia (CLL) (88), non-small cell lung cancer (NSCLC) (89) and endometrial stromal sarcoma (ESS) (Table IV) (90). HELQ is an important regulator of cancer proliferation, invasion, migration and can contribute to poor patient prognosis and platinum resistance through several mechanisms (13,86,87) in different types of tumors (Fig.…”
Section: Potential Roles Of Helq In Tumorigenesis and Underlying Mech...mentioning
confidence: 99%
See 1 more Smart Citation